Comparison of Total Body Irradiation–based Versus Chemotherapy-based Conditionings for Early Complications of Allogeneic Hematopoietic Stem Cell Transplantation in Children With ALL. Issue 7 (October 2021) - Yalcin, Koray; Pehlivan, Berrin; Celen, Suna; Bas, Elif Gulsah; Kabakci, Canan; Pashayev, Dayanat; Daloglu, Hayriye; Zhumatayev, Suleyman; Uygun, Vedat; Karasu, Gulsun Tezcan; Hazar, Volkan; Yesilipek, Akif
Abstract : Background: Total body irradiation (TBI) is the cornerstone of conditioning regimens in pediatric hematopoietic stem cell transplantation for acute lymphoblastic leukemia. As the late effects and survival comparison between TBI and chemotherapy were well analyzed before, in this study, we aim to focus on the first 100 days and early complications of transplantation. Methods: This retrospective study involves 72 pediatric patients (0 to 18 y) underwent first hematopoietic stem cell transplantation for acute lymphoblastic leukemia between October 2015 and May 2019. Patients are divided into 2 groups regarding conditioning regimens. Conditionings includes either TBI 1200 cGy/6 fractions/3 days and etoposide phosphate or busulfan, fludarabine, and thiotepa. Busulfan was administered IV and according to body weight. Results: The incidences of acute graft versus host disease grade 2 to 4, veno-occlusive disease, capillary leakage syndrome, thrombotic microangiopathy, blood stream infection, hemorrhagic cystitis and posterior reversible encephalopathy syndrome before day 100 were similar for both conditioning regimens; however, patients received TBI-based conditioning had significantly longer neutrophil engraftment time (17.5 vs. 13 d, P =0.001) and tended to have more engraftment syndrome (ES) (45.5% for TBI vs. 24.0% for chemotherapy, P =0.069). Multivariate analysis showed that TBI-based conditioning was associated with a longer neutrophil engraftment time (hazard ratio [HR]=1.20, P =0.006), more cytomegalovirus (CMV) reactivation (HR=3.65, P =0.038) and more ES (HR=3.18, P =0.078). Conclusions: Our findings support chemotherapy-based regimens with early neutrophil engraftment, less ES and CMV reactivation compared with TBI. Although there is no impact on survival rates, increased incidence of ES and CMV reactivation should be considered in TBI-based regimens.